Reuse of water and agroindustrial effluent in the production of soursop seedlings - Azevedo, Patrícia Roque Lemos (2019)
The climatic conditions of the semiarid region of the northeast, characterized by the deficiency of rainfall, give irrigation a fundamental importance as one of the instruments to enable the viability of more agriculture Productive and with lower risk. Given the panorama of water scarcity, this paper aims to propose the development of soursop seedlings from the utilization of air conditioning and agroindustrial effluent. The research was developed in the seedling production sector located at the Federal Institute of Paraíba, Campus Sousa. A completely randomized block design was used, with five treatments and four replications. The treatments resulted from the following combinations: T1 = 100% Artesian Well, T2 = 100% air conditioning, T3 = combination 50% air conditioning + 50% Artesian Well, T4 = combination 50% agroindustrial effluent + 50% air conditioning and T5 = 100% agroindustrial effluent. Soursop seedlings were produced in plastic bags using Neossol Fluvic and manure in proportion (2:1) as substrate. The following variables were evaluated: plant height, stem diameter, number of leaves, green and dry mass of aerial part and root and influence on soil attributes (PH, P, K, Na, Ca, Mg, MO, PST). After the study, it was verified that the use of air-conditioning water is a good alternative as a source of irrigation for the seedlings of Gravioleira, while the water of agroindustrial effluent was not adequate for this purpose, since it influenced Negatively in most of the variables analyzed.